Leveraging Facebook for Marketing Campaigns: Exploring the Advertising Potential of Facebook (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Social media tools like Facebook have rapidly turned out to be too mainstream and too much used by users and businesses. Advertisers attempt to discover the most ideal approach to publicize their products on Facebook keeping in mind the end goal to establish relationship with users and engage them with the brand. Facebook particularly portrays itself as the ideal promoting platform since its developers have made a promotion system which enables organizations to utilize the data of each Facebook user for customized advertising. Thus, marketers are leveraging Facebook to promote their products and brands and simultaneously communicate with their users so as to engage them and create a good impression of the brand. This paper attempts to find out the basic as well as advanced features tools of Facebook that a marketer is using for promotion purposes.